THE ROLE OF SELF COMPASSION AND RELIGIOSITY IN FACING ACADEMIC ANXIETY IN FINAL-YEAR STUDENT AT FPIP UMSIDA - Brienda Rifco Salsabila; Lely Ika Mariyati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Anxiety related to writing a thesis is a common problem experienced by senior students due to academic demands, time preassure, and concerns about reserch outcomes. Self-compassion and religiosity are viewed as factors that can help students manage anxiety during the thesis-writing process. This study aims to examine the role of self-compassion and religiosity in relation to anxiety associated with writting a thesis among senior students in the faculty of psychology and educational sciences at Muhammadiyah University of Sidoarjo. The study employed a quantitative correlational approach and a purposive sampling technique involving 260 senior students as respondents. The measurment instrumen used in this study were scales measuring self-compassion, religiosity, and anxiety related to writing a thesis, all of which had been validated for validity and reliability. Data analysis was conducted using multiple linear regression via SPSS software. The findings of this study indicate that religiosity and self-compassion are psychological factors that play a significant role in helping senior students cope with academic pressure during the thesis writing process.